Taxa de conversão para demência em uma coorte de idosos residentes na comunidade, São Paulo Brasil, com clinical dementia de 0 ou 0,5. - Montaño, Maria Beatriz Marcondes Macedo [UNIFESP] (2010)
Introduction: Incidence of dementia is a major public health problem in aging populations, particularly in developing countries where the elderly population has grown explosively. Identification of risk groups is vital to implement health promotion. The Clinical Dementia Rating (CDR) is a valid scale to classify the severity of dementia cases (mild, moderate, severe), also enabling the identification of borderline cases, when the subject has no longer a normal cognitive status for his age, but hasn’t met criteria for dementia yet. There are many evidences that this group has a significantly higher rate of conversion to dementia than the normal group. Objective: This study aims to verify the conversion rate to dementia in a cohort of elderly (70+) living in São Paulo, a large urban center in Brazil, particularly among borderline cases with a CDR=0.5, and to identify associated factors. Methodology: A sample with 156 members of the cohort (n=440) included all the elderly with a MMSE below 26 and a sample of those with a MMSE equal or above 26, all clinically evaluated for dementia including a Neuropsychological Battery (NPB) at baseline. A Portuguese version of CDR (previously validated by authors) was applied to the closest relative or carer. After refusals and deaths, 95 elderly were re-evaluated after an average 2.6-years interval. The cumulative conversion rate of dementia was compared among demographic characteristics, mental health, Activities of Daily Living (ADL), vascular risk factors, NPB performance and initial classification of CDR, using Poisson Regression methods in both the univariate analysis and the multivariate analysis, with natural logarithm of exposure time as an offset variable. The value of significance accepted was 0.05. Results: 95 elderly were re-evaluated, but 15 were demented at baseline and not included in the present analysis. The majority of those studied (n=80) was women (72%), the average age was 80.7 years, and 20% were illiterate, while 21% had 8 or more years of education. Among those at risk of converting to dementia, 50% had a CDR 0 at baseline and 50% a CDR 0.5 - 70% with sum of boxes scores equals 1 or below, and 30% with sum of boxes scores greater than 1. The conversion rate of dementia in the period was 91.3/1000 person-years and there were no significant differences between the rates of conversion according to age, years of education, gender, mental health, altered NPB, presence of vascular risk factors and degree of independence in the ADL, at baseline. There was a significantly higher incidence rate among those with a CDR 0.5, and most importantly among those with a sum of the boxes scores greater than 1 at baseline, with a relative risk of 5.69 higher compared to CDR 0. In the multivariate analysis, the CDR 0.5 and the sum of the highest boxes scores were the only variables that were independently associated with a higher conversion rate to dementia. Discussion: The conversion rate to dementia was high, as expected given the cohort’s advanced age. The conversion rate to dementia, in the period observed, was higher among those with CDR=0.5 and higher if the sum of the boxes scores was above one. Those were the only variables independently associated to conversion. Hence, the CDR must be recommended in the clinical practice with elderly to identify those at a greater risk of dementia.